Giải bài toán k-median nhờ quy hoạch lõm - Toàn, Nguyễn Trọng; Nghĩa, Nguyễn Đức (Journal of Computer Science and Cybernetics, 2016)
The k-median problem sonsits of locating k facilities on a network of n nodes, so that sum of shortest distances from each of the nodes of the network to ist nearest facilities is minimized. Based on the reasonable evaluation of bounds, a branch and bound algorithm for the problem is proposed. Its computational experience is also presented in order to compare it with other methods.